The abandoned empress. 4 - 인아 (Yen Press, 2023)
"Out in the peaceful countryside, far away from the painful memories of the Imperial Capital, Aristia hopes to recuperate and focus on her sword training. However, she soon finds out the hard way that it's not so easy to escape fate. As Ruveliss's unexpected visit rekindles the deep-seated trauma in her heart, can Tia find the strength cut a new path for herself? "-- Amazon.com.